Airborne DOAS limb measurements of tropospheric trace gas profiles: case study on the profile retrieval of O4 and BrO - Prados-Roman, C.; Butz, A.; Deutschmann, T.; Dorf, M.; Kritten, L.; Minikin, Andreas; Platt, U.; Schlager, Hans; Sihler, H.; Theys, N.; Van Roozendael, M.; Wagner, T.; et al. (Atmospheric Measurement Techniques, 2011)
A novel limb scanning mini-DOAS spectrometer for the detection of UV/vis absorbing radicals (e.g., O3, BrO, IO, HONO) was deployed on the DLR-Falcon (Deutsches Zentrum fÃÂ¼r Luft- und Raumfahrt) aircraft and tested during the ASTAR 2007 campaign (Arctic Study of Tropospheric Aerosol, Clouds and Radiation) that took place at Svalbard (78ÃÂ° N) in spring 2007. Our main objectives during this campaign were to test the instrument, and to perform spectral and profile retrievals of tropospheric trace gases, with particular interest on investigating the distribution of halogen compounds (e.g., BrO) during the so-called ozone depletion events (ODEs). In the present work, a new method for the retrieval of vertical profiles of tropospheric trace gases from tropospheric DOAS limb observations is presented. Major challenges arise from modeling the radiative transfer in an aerosol and cloud particle loaded atmosphere, and from overcoming the lack of a priori knowledge of the targeted trace gas vertical distribution (e.g., unknown tropospheric BrO vertical distribution). Here, those challenges are tackled by a mathematical inversion of tropospheric trace gas profiles using a regularization approach constrained by a retrieved vertical profile of the aerosols extinction coefficient EM. The validity and limitations of the algorithm are tested with in situ measured EM, and with an absorber of known vertical profile (O4). The method is then used for retrieving vertical profiles of tropospheric BrO. Results indicate that, for aircraft ascent/descent observations, the limit for the BrO detection is roughly 1.5 pptv (pmol molÃ¢ÂÂ1), and the BrO profiles inferred from the boundary layer up to the upper troposphere and lower stratosphere have around 10 degrees of freedom. For the ASTAR 2007 deployments during ODEs, the retrieved BrO vertical profiles consistently indicate high BrO mixing ratios (Ã¢ÂÂ¼15 pptv) within the boundary layer, low BrO mixing ratios (Ã¢ÂÂ¤1.5 pptv) in the free troposphere, occasionally enhanced BrO mixing ...